An Analysis on Welfare Schemes for Women’s Empowerment in Himachal Pradesh - Mansoori, Rukhsar (International Journal of Law, Human Rights and Constitutional Studies, 2022)
The idea of self-empowerment is intrinsically linked to power. It is lost from the route where it does not exist insufficiently, which is where it does not exist at all. To equip women to be economically independent, to have good self-esteem that enables them to confront any tough circumstance, to be self-reliant and to be able to engage in many forms of development activity is what we mean when we talk about the empowerment of women. It is imperative that women in positions of power always have a voice in the decision-making process. Both the Ministry of Human Resource Development and the National Commission for Women (NCW) in India are continuously working toward the goal of protecting the rights and legal entitlements of women. The 73rd and 74th Amendments (1993) to the Constitution of India provided some special powers to women, such as the reservation of seats (33%). On the other hand, the report HRD as of March 2002 shows that the legislatures with the highest percentage of women are those in Find land (36%), Iceland (34.9%), Sweden (42.7%) and Denmark (38%). At the very least on the level of the village, “The New Panchayati Raj” in India is a component of the movement to give women more power.